One-company towns: Scale and consequences - Simon Commander (IZA World of Labor, 2018)
One-company towns are a relatively rare phenomenon. Mostly created in locations that are difficult to access, due to their association with industries such as mining, they have been a marked feature of the former planned economies. One-company towns typically have high concentrations of employment that normally provide much of the funding for local services. This combination has proven problematic when faced with shocks that force restructuring or even closure. Specific policies for the redeployment of labor and funding of services need to be in place instead of subsidies simply aimed at averting job losses.
Keywords: D24; J42; R23; 330; employment concentration; worker attachment; restructuring; unemployment